2019
DOI: 10.3389/fpsyt.2019.00889
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition and Impulsive Choice in Relation to Methamphetamine Use and Psychosis Symptoms

Abstract: Introduction:The cognitive profiles of people with methamphetamine use disorder are characterized by impulsivity and impairment in social cognition. However, previous studies have not fully accounted for the presence and impact of co-occurring mental health problems on these domains. For instance, psychotic symptoms are commonly experienced by people who use methamphetamine and may influence cognitive performance. We aimed to examine decision making and emotion recognition in individuals with methamphetamine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…As stated earlier, the selected studies are the one on the schizophrenia population that didn't excluded METH users and the studies on METH users that didn't excluded participants with a psychotic disorder. Among those 17 studies, only two looked at the difference between METH users with and without psychosis 44,45 . Furthermore, the Table illustrates how certain domains of social cognition merit to be studied in METH users, as well as in MIPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated earlier, the selected studies are the one on the schizophrenia population that didn't excluded METH users and the studies on METH users that didn't excluded participants with a psychotic disorder. Among those 17 studies, only two looked at the difference between METH users with and without psychosis 44,45 . Furthermore, the Table illustrates how certain domains of social cognition merit to be studied in METH users, as well as in MIPD.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies, including a meta-analysis, mentioned social knowledge and attributional biases 56,57 , with a third one mentioning social perception as well 46 . With deficits in ToM and emotion recognition being the main focus in most studies 44,48,49,57 , more research is warranted on social knowledge, attributional biases and social perception, as these are also important domains of social cognition. In the literature, studies (that excluded comorbidity profiles) have reported that deficits in social cognition have a considerable impact on social functioning in people with schizophrenia 64,65 and in stimulant users [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta impulsividad como rasgo de personalidad es frecuentemente relacionada con la búsqueda de sensaciones y la necesidad de experimentar variadas conductas de riesgo, por sus refuerzos inmediatos (Arunogiri et al, 2019;Gámez & Villa, 2015;Gutiérrez et al, 2013). Se ha observado que la impulsividad es mayor en jóvenes con adicción a diferencia de aquellos que no presentan alguna adicción (Pérez-Fuentes et al, 2015) y se define como la tendencia de los adolescentes a hacer las cosas sin pensar, por lo que en muchos casos no logran anticipar las consecuencias positivas o negativas de sus conductas (Limonero et al, 2013).…”
Section: Iscusiónunclassified
“…5 Increasing evidence suggests that individuals with MUD have an impaired ability to correctly identify emotions and infer the mental state of others. [19][20][21][22] Specifically, individuals with MUD are less empathetic and have more difficulty understanding another's thoughts, feelings and intentions. Many studies with drug-free participants have demonstrated that impairments in empathy or theory of mind are associated with antisocial or offending behaviours.…”
Section: Introductionmentioning
confidence: 99%